The Boggart Sourcebook Texts and Memories for the Study of the British Supernatural - Young, Simon (University of Exeter Press, 2022)
Comprising three parts, this book is a companion volume to The Boggart: Folklore, History, Place-Names and Dialect. Part one, 'Boggart Ephemera', is a selection of about 40,000 words of nineteenth-century boggart writing (particularly material that is difficult to find in libraries). Part two presents a catalogue of 'Boggart Names' (place-names and personal names, totalling over 10,000 words). Finally, part three contains the entire 'Boggart Census' - a compendium of ground-breaking grassroots research. This census includes more than a thousand responses, totalling some 80,000 words, from older respondents in the north-west of England, to the question: 'What is a boggart?' The Boggart Sourcebook will be of interest to folklorists, historians and dialect scholars. It provides the three corpora on which the innovative monograph, The Boggart, is based.